‘Finestre’ Post-sovietiche. La letteratura russofona d’Ucraina come laboratorio di identità culturale - Marco Puleri (Altre Modernità, 2015)
This paper is focused on the complex situation linked with the concept of national cultural identity, and the conflicts between cultural models, which reflect social and political struggles in the post-Soviet space. The analysis of contemporary Ukrainian literature in Russian represents a productive field of research in order to analyse the post-soviet national context. Such a literary phenomenon emerges in the interstitial passage between Ukrainian fixed opposite identifications: we deal with a hybrid phenomenon that grows out of the passage from the soviet domination to national independence, and that produces a narrative of displacement. The given literary movement rises at the margins of the national cultural model and is an example of post-soviet hybrid writing, which stimulates the process of confrontation: as stressed by Jurij Lotman (1994), every culture creates its own ‘marginal system’, which involves outsiders who don’t belong to its centre, and that a strict analysis excludes from its model.